Restless nation : starting over in America - Jasper, James M., 1957- (University of Chicago Press, 2000)
In Restless Nation, James M. Jasper isolates a narrative that lies very close to the core of the American character. From colonial times to the present day, Americans have always had a deep-rooted belief in the "fresh start"--A belief that still has Americans moving from place to place faster than the citizens of any other nation